Early feeding leads to molecular maturation of the gut mucosal immune system in suckling piglets - Choudhury, Raka; Gu, Yuner; Bolhuis, J. Elizabeth; Kleerebezem, Michiel (Frontiers in Immunology, 2023)
Diet-microbiota-host interactions are increasingly studied to comprehend their implications in host metabolism and overall health. Keeping in mind the importance of early-life programming in shaping intestinal mucosal development, the pre-weaning period can be utilised to understand these interactions in suckling piglets. The objective of this study was to investigate the consequences of early-life feeding on the time-resolved mucosal transcriptional program as well as mucosal morphology. A customised fibrous feed was provided to piglets (early-fed or EF group; 7 litters) from five days of age until weaning (29 days of age) in addition to sow’s milk, whereas control piglets (CON; 6 litters) suckled mother’s milk only. Rectal swabs, intestinal content, and mucosal tissues (jejunum, colon) were obtained pre- and post-weaning for microbiota analysis (16S amplicon sequencing) and host transcriptome analysis (RNA sequencing). Early feeding accelerated both microbiota colonisation as well as host transcriptome, towards a more “mature state”, with a more pronounced response in colon compared to jejunum. Early feeding elicited the largest impact on the colon transcriptome just before weaning (compared to post-weaning time-points), exemplified by the modulation of genes involved in cholesterol and energy metabolism and immune response. The transcriptional impact of early feeding persisted during the first days post-weaning, and was highlighted by a stronger mucosal response to the weaning stress, via pronounced activation of barrier repair reactions, which is a combination of immune activation, epithelial migration and “wound-repair" like processes, compared to the CON piglets. Our study demonstrates the potential of early-life nutrition in neonatal piglets as a means to support their intestinal development during the suckling period, and to improve adaptation during the weaning transition.